Chiral (S)-5-octyloxy-2-[{4-(2-methylbuthoxy)-phenylimino}-methyl]-phenol liquid crystalline compound as additive into polymer solar cells - Canli, N. Yilmaz; Gunes, S.; Pivrikas, A.; Fuchsbauer, A.; Sinwel, D.; Sariciftci, N. S.; Yasa, Oe.; Bilgin-Eran, B. (ELSEVIER, 2010)
We have investigated the effect of new chiral (S)-5-octyloxy-2-[{4-(2-methylbuthoxy)-phenylimino}-methyl]-phenol liquid crystalline compound (LC) addition into bulk-heterojunction solar cells, based on poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C-61-butyric acid methyl ester (PCBM) mixtures. Based on current-voltage characteristics and transient charge carrier extraction by linearly increasing voltage (CELIV) measurements, the efficiency of devices with liquid crystal is found to be higher than that of devices from pristine blends of P3HT-PCBM. It is found that the charge carrier mobility increased significantly in the devices with liquid crystals. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Liquid crystal; Organic solar cells; Polymer solar cells; Conjugated polymers; ORGANIC PHOTOVOLTAICS; CHARGE-TRANSPORT; POSTPRODUCTION TREATMENT; LARGE-AREA; POLY(3-HEXYLTHIOPHENE); POLYTHIOPHENE; PHOTODIODES; PERFORMANCE; FABRICATION; RELAXATION; Energy & Fuels; Materials Science; Physics